The study of language from the perspective of cultural studies - Eva Sulastri Sagita; Mustakim Sagita (Yayasan Sagita Akademia Maju, 2024)
The emergence of cultural studies has expanded the scope of understanding and engaging with many cultural phenomena. Language, essential to the concept of culture, has taken on a more significant and purposeful function. Linguistics must adapt to include wider perspectives to align with the greater understanding of culture as the foundation of linguistics. In this scenario, linguistics must rely on the following assumptions: (1) language is not impartial or neutral, (2) language is concerned with the concept of representation, (3) language is intertwined with power dynamics, and (4) language is connected to the act of expressing thoughts and ideas. These points are significant in the advancement of cultural studies